The effectiveness of filtering glycopeptide peak list files for Y ions. (17th February 2020) - Chalkley, Robert J.; Medzihradszky, Katalin F.; Darula, Zsuzsanna; Pap, Adam; Baker, Peter R.
Abstract : Novel software workflow for identifying additional glycopeptides in complex datasets. Abstract : Intact glycopeptide analysis is becoming more common with developments in mass spectrometry instrumentation and fragmentation approaches. In particular, collision-based fragmentation approaches such as higher energy collisional dissociation (HCD) and radical-driven fragmentation approaches such as electron transfer dissociation (ETD) provide complementary information, but bioinformatic strategies to utilize this combined information are currently lacking. In this work we adapted a software tool, MS-Filter, to search HCD peak list files for predicted Y ions based on matched EThcD results to propose additional glycopeptide assignments. The strategy proved to be extremely powerful for O -glycopeptide data, and also of benefit for N -linked data, where it allowed rescue of low confidence results from database searching.